Determinants of behavioral intentions to screen for prostate cancer in Omani men - Joshua Kanaabi Muliira; Hazaa Sami Al-Saidi; Asaad Nasser Al-Yahyai (Elsevier, 2017)
Objective: This study aimed at exploring the perceived barriers and intention to screen for prostate cancer (PCa). Methods: A survey questionnaire and a descriptive design were used to collect data from 129 Omani men above the age of 40 years. The questionnaire comprised the International Prostate Symptom Score (IPSS), barriers, and intention to screen scales. The participants were recruited from barbershops located in two cities of Oman. Results: The mean IPSS score was 8.31 ± 3.34 and the majority of participants had mild prostate cancer symptoms (60.4%). The others had moderate (28.7%) or severe symptoms (10.9%). Most men had low-to-moderate intention to screen using the method of digital rectal examination (DRE) (76%) and prostate-specific antigen test (PSA) (69.8%). The most common barriers to screening were fear of finding out something wrong (48.1%), not knowing what will be done during screening (54.3%), belief that PCa is not a serious disease (55.8%), and belief that DRE is embarrassing (56.6%). The significant determinants of intention to screen using DRE were perceived threat of the disease (P = 0.006) and past information from doctors that one has any prostate disease (P = 0.017). The determinants of intention to screen using PSA were perceived threat of the disease (P = 0.025), perceived general health (P = 0.047), and past information from doctors that one has any prostate disease (P = 0.017). Conclusions: The participants had diminutive intention to undergo PCa screening. Interventions aimed at enhancing PCa disease and risk awareness may help to reduce the barriers and increase PCa screening uptake.